2010
DOI: 10.1111/j.1399-0012.2009.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug management in emergent liver transplantation of mitochondrial disorder carriers: review of the literature

Abstract: There are no randomized, controlled, trial-based indications regarding safe anesthetic drugs to be used perioperatively in MRCD carriers. Consultation among geneticists, anesthesiologists, intensivists, and surgeons is essential in patients with known/suspected metabolic syndrome for planning appropriate perioperative care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Because of a wide variety of symptoms and severity in mitochondrial disorders, selection of medications requires considerable attention for each patient. Drug management for LT anesthesia in mitochondrial disorders is well discussed in a review by Vater et al .…”
Section: Other Issuesmentioning
confidence: 99%
“…Because of a wide variety of symptoms and severity in mitochondrial disorders, selection of medications requires considerable attention for each patient. Drug management for LT anesthesia in mitochondrial disorders is well discussed in a review by Vater et al .…”
Section: Other Issuesmentioning
confidence: 99%
“…However, the researchers concluded that patients with mitochondrial disease should not be excluded from transplantation [12]. Finally, an article published by Vater and colleagues reviewed existing literature on transplantation patients with mitochondrial disorders and reported a case of an emergent liver transplant [13]. The article discussed both the paucity of literature on perioperative management of transplant recipients with mitochondrial disorders as well as the conflicting nature of reports with safety of anesthesia and perioperative drugs.…”
Section: Discussionmentioning
confidence: 99%